Community Foundation: A New Idea to Promote the Development of Community Autonomy - Liu, Jianwen (International Journal For Research In Social Science And Humanities, 2021)
Community Fund Association was invented and developed in America. The Community Fund Association is based on the principles of democracy, and it appreciates the loyalty and thoughtfulness to the members of the community. This point has influenced the construction of the community effectively.